Analisis Sistem Proteksi dan Koordinasi Relay Overcurrent pada Jaringan Distribusi Menggunakan ETAP - Hasan Yanmar Lubis; Debi Rahmadani; Lorencya Elisabet Br Sembiring; Michael Sitorus; Desman Jonto Sinaga (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to evaluate the response and coordination of overcurrent relays (OCR) in a simulated electrical power distribution system using ETAP. The system was modeled through a single-line diagram, followed by load flow and balanced three-phase fault simulations. The simulation at Bus B6 (0.41 kV) produced a three-phase fault current of 3.523 kA. Fault isolation operated selectively, where OCR8, located at the most downstream protection zone, responded the fastest with an operating time of 0.345 s, while OCR7 and OCR3 operated later as backup layers with coordinated time grading and no relay overlap. The decreasing fault current trend across the 20 kV buses confirms the influence of line impedance and distance, consistent with fundamental short-circuit theory. This study demonstrates that coordinated OCR schemes can serve as an initial academic reference before adaptation to real systems.